0407 An old trade with an unanswered question: does arc-welding fume exposure increase the risks of obstructive pulmonary diseases? First findings from the WELSHIP cross-sectional study. (23rd June 2014) - Marongiu, Andrea; Hasan, Omer; Ali, Anila; Bakhsh, Sharoon; George, Bobby; Irfan, Nabeel; Canova, Cristina; Schofield, Susie; Szram, Joana; Minelli, Cosetta; Cullinan, Paul
Abstract : Objectives: Increasingly, global manufacturing is shifting to emerging economies and with it the use of arc-welding for applications in different industries. The chronic respiratory adverse effects resulting from exposure to gases and ultrafine metal particles in welding fume are incompletely understood. We aimed to measure the prevalence of arc-welding related pulmonary obstructive outcomes by analysing data collected in a shipyard in the Middle East. Method: Between January and December 2013, through cross-sectional survey, we collected spirometry data and behavioural, occupational and respiratory symptoms information from a random sample of male shipyard workers; 397 were exposed to welding fume and 127 were non-exposed. The sample was selected from a total population of about 8000 employees, by frequency matching for ethnicity and age relatively to full-time welders ('highly' exposed). Results: Of the 580 workers invited, 26 subsequently left their job; of the remainder, 95%(524) agreed to participate. The participants, from the Indian subcontinent (90%) or Philippines (10%), had a median age of 38 years. Ever smoking was reported by 37%, with full-time welders reporting the lowest proportion of current smoking, 18%(24/131). Overall, 13% reported respiratory symptoms with a higher prevalence in the winter months. Post-bronchodilator spirometry data were available for 91% of workers. Mean values for FEV1 and FVC were 2.87L and 3.48L, with no statistically significant differences across exposure groups (p-values: 0.71 and 0.48). Conclusions: These preliminary results need to be explored further in relation to smoking, past and current occupational exposure. This population, it is hoped, will form the basis for a longitudinal study.